2017
DOI: 10.1177/2167479517711450
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Family Communication Patterns and the Self-Efficacy of Student-Athletes

Abstract: The coach–athlete relationship and coach communication have received significant attention, as they relate to athlete performance variables; however, the coach alone does not shape an athlete’s experiences. Research has indicated the importance of the parent/guardian’s role in athlete development and suggests parent/guardian communication may also have implications for athlete performance outcomes. Of such performance variables, self-efficacy has been demonstrated to have a consistent positive and moderate rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…In terms of realizing the ways of communication, it is observed that men are better in the framework, Erdner and Wright (2017) emphasized that their parents should be encouraged to communicate with athletes positively, helping them to dream for success.While all these stresses show the importance of communication between the sports instructor and the parents, the lack of communication at the desired level is significant. In line with these results, it can be said that there is no communication between coaches and parents to the extent desired by coaches.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of realizing the ways of communication, it is observed that men are better in the framework, Erdner and Wright (2017) emphasized that their parents should be encouraged to communicate with athletes positively, helping them to dream for success.While all these stresses show the importance of communication between the sports instructor and the parents, the lack of communication at the desired level is significant. In line with these results, it can be said that there is no communication between coaches and parents to the extent desired by coaches.…”
Section: Resultsmentioning
confidence: 99%
“…Also, courageously and higher resilience [38] overcome difficulties and problems. William Good believed that the family as the most important institution of society succeeds in following ways in the child's socialization process: having effective relationships with the child, known authority, having a role model, sustaining relationships, giving freedom to the child, communication with explanation and reason, punishment and appropriate encouragement [39].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, trainers can develop Life Control within sportspersons through the referencing of previous achievements and accomplishments and imagining optimal performance (Erdner and Wright, 2018). These interventions are likely to be associated with heightened self-efficacy, the individual's belief in their ability to succeed in specific situations (Munroe-Chandler et al, 2008).…”
Section: The Mtq48 and The Negative Psychological Effects Of Covid-19mentioning
confidence: 99%